Relationship Between Physical Activity, Parental Psychological Control, Basic Psychological Needs, Anxiety, and Mental Health in Chinese Engineering College Students During the COVID-19 Pandemic - Liu, Zongyu; Li, Meiran; Ren, Chuanqi; Zhu, Guangyu; Zhao, Xiuhan (Frontiers in Psychology, 2022)
The issue of mental health among college students is of increasing concern during the COVID-19 outbreak. Since course characteristics of engineering college students determine the particularities of their mental health, the specific objectives of this study were: (1) to analyze the relationship between physical activity, parental psychological control, basic psychological needs, anxiety, and mental health in Chinese engineering college students during COVID-19 pandemic; and (2) to examine the mediation effect of anxiety between the relationship of basic psychological needs and mental health. A cross-sectional study was conducted among several universities in Shandong Province, China. We randomly selected 254 Chinese engineering college students from these colleges. Participants who were given questionnaires completed the Physical Activity Rating Scale (PARS-3), Basic Needs Satisfaction in General Scale (BNSG-S), Parental psychological control Questionnaire, the Beck anxiety inventory (BAI), and the Kessler 10 (K10) scale. The mediation model was conducted to assess the mediation effect of anxiety between the relationship of basic psychological needs and mental health. Among 254 Chinese college students majoring in engineering, the results showed that their mental health was in the mid-level range. Besides, physical activity and basic psychological needs is positively correlated with mental health, respectively, while parental psychological control is not correlated with mental health. Anxiety is negatively associated with mental health. Mediation analysis revealed that anxiety played a mediation role in the relationship between basic psychological needs and mental health. In conclusion, mental health of Chinese engineering college students deserves extensive attention during the COVID-19 pandemic. Proper intervention on physical activity, basic psychological needs, and anxiety may be beneficial to improve their mental health. In addition, meeting basic psychological needs is beneficial to reduce anxiety and improve mental health further.